2010
DOI: 10.1002/stem.294
|View full text |Cite
|
Sign up to set email alerts
|

Foxa2 and Nurr1 Synergistically Yield A9 Nigral Dopamine Neurons Exhibiting Improved Differentiation, Function, and Cell Survival

Abstract: Effective dopamine (DA) neuron differentiation from neural precursor cells (NPCs) is prerequisite for precursor/ stem cell-based therapy of Parkinson's disease (PD). Nurr1, an orphan nuclear receptor, has been reported as a transcription factor that can drive DA neuron differentiation from non-dopaminergic NPCs in vitro. However, Nurr1 alone neither induces full neuronal maturation nor expression of proteins found specifically in midbrain DA neurons. In addition, Nurr1 expression is inefficient in inducing DA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 54 publications
4
84
0
1
Order By: Relevance
“…Here, we showed that co-expression of the anti-apoptotic factor Bcl-xL along with BAM (BAMX) led to iNPCs that were highly proliferative over a long period of time and grew over 100 passages without alterations in major NPC properties. Numerous roles of Bcl-xL in NPC survival and maintenance have been documented previously in knock-out mouse embryonic brains (16), in vitro with gain-of-function studies using NPC cultures (30,31), and in clonal analyses using mouse embryonic neural precursor cells transduced with Bcl-xL (data not shown). To investigate whether the observed effects of Bcl-xL were due to its pro-survival functions, we analyzed the effect of Bcl-xL on the conversion of fibroblasts to iNPCs using dimerization-and mitochondrial localization-deficient Bcl-xL mutants (18).…”
Section: Discussionmentioning
confidence: 84%
“…Here, we showed that co-expression of the anti-apoptotic factor Bcl-xL along with BAM (BAMX) led to iNPCs that were highly proliferative over a long period of time and grew over 100 passages without alterations in major NPC properties. Numerous roles of Bcl-xL in NPC survival and maintenance have been documented previously in knock-out mouse embryonic brains (16), in vitro with gain-of-function studies using NPC cultures (30,31), and in clonal analyses using mouse embryonic neural precursor cells transduced with Bcl-xL (data not shown). To investigate whether the observed effects of Bcl-xL were due to its pro-survival functions, we analyzed the effect of Bcl-xL on the conversion of fibroblasts to iNPCs using dimerization-and mitochondrial localization-deficient Bcl-xL mutants (18).…”
Section: Discussionmentioning
confidence: 84%
“…In addition, exogenous Nurr1 failed to induce markers specific to the midbrain (Lee et al, 2010). These issues could be addressed by co-expressing Foxa2, known to induce the expression of numerous midbrain-specific genes and facilitate Nurr1-induced DA neuron differentiation (Lee et al, 2010). As Foxa2 has a different expression pattern from Nurr1 during midbrain development, this strategy requires the development of another efficient inducible system, in which the expression of multiple genes could be controlled simultaneously but independently, based on their individual developmental patterns.…”
Section: Research Reportmentioning
confidence: 97%
“…S9). In addition, exogenous Nurr1 failed to induce markers specific to the midbrain (Lee et al, 2010). These issues could be addressed by co-expressing Foxa2, known to induce the expression of numerous midbrain-specific genes and facilitate Nurr1-induced DA neuron differentiation (Lee et al, 2010).…”
Section: Research Reportmentioning
confidence: 99%
“…3C). Because total cell numbers were not significantly altered by shFoxa2 treatment (data not shown), the Foxa2 effect on cell proliferation (Lee et al, 2010) is not likely to have influenced the DA gene expression data, although this possibility cannot be completely excluded. Forced Nurr1 expression yielded a few TH + DA cells in NPC cultures derived from non-dopaminergic embryonic cortical tissues (Fig.…”
mentioning
confidence: 97%